Pengaruh Akuntansi Hijau Dan Kinerja Lingkungan : Analisis Bibliometrik - Atiyah, Ummi Waqiatul; Herli, Mohammad (SUSTAINABLE, 2025)
This study is intended to identify recent research developments related to the topic of green accounting and its correlations with sustainability performance. The analysis was conducted using R Biblioshiny for initial visualization, and VOSviewer for research network mapping and topic clustering. The study involved at least 1684 documents published between 1991 and early 2024. The study found a progress in research related to green accounting and sustainability performance. According to affiliation and country, green accounting and sustainability performance research is dominated by China. There are ten clusters formed, such as sustainability and green economy, as well as sustainability performance and sustainability economy. This study provides researchers with an understanding of the dynamics of green accounting and sustainability performance research and suggests potential areas of emerging research. While this research appears to have been conducted thoroughly, it is limited by the coverage of the Scopus database, which may not include all relevant publications. The originality of this study lies in the use of a systematic bibliometric approach to analyze green accounting and sustainability performance, which has not been done in the previous literature.